Family CEO and board service: Turning the tide for export scope in family SMEs. Issue 5 (October 2019) - Bauweraerts, Jonathan; Sciascia, Salvatore; Naldi, Lucia; Mazzola, Pietro
Highlights: We study how family management and governance affect family SMEs' export scope. The presence of a family CEO in family SMEs negatively affects export scope. At high levels of board service, family CEOs positively influence export scope. Abstract: Adopting the socioemotional wealth perspective, we argue that the presence of a family CEO in family SMEs negatively affects export scope, but that such negative effect is mitigated by board service. We develop and test a model that considers the synergistic combination of family management and another important aspect of family governance in the context of family firm internationalization: the service behavior of the board of directors. The empirical evidence from a sample of 248 Belgian family SMEs shows that governance is crucial to overcoming the problems of family management: family CEOs may negatively influence export scope, but board service is able to turn the tide so that the family CEO effect becomes positive. With such novel findings, we contribute to international business and family business studies